2018
DOI: 10.1101/450577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative mode of action of antimicrobial peptide melimine and its derivative Mel4 against Pseudomonas aeruginosa

Abstract: Society for Microbiology annual meetings in 2017. There are no conflicts of interest for any 31 of the authors that could have influenced the results of this work. Prof. Mark Willcox holds 32 the patent for the melimine peptide. 33 2 ABSTRACT 34Melimine and Mel4 are chimeric cationic peptides with broad spectrum antimicrobial 35 activity, and recent investigations have shown that they are highly biocompatible with animal 36 model and human clinical trials. The current study examined the mechanism of acti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…The results of the interaction of surface-bound melimine and Mel4 with P. aeruginosa was similar to that found with these peptides in solution (Yasir et al, 2019). However, the time course of interaction and disruption of cell membranes by FIGURE 4 | Inner membrane permeabilization.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The results of the interaction of surface-bound melimine and Mel4 with P. aeruginosa was similar to that found with these peptides in solution (Yasir et al, 2019). However, the time course of interaction and disruption of cell membranes by FIGURE 4 | Inner membrane permeabilization.…”
Section: Discussionsupporting
confidence: 75%
“…If 11% of the melimine was released into the 200 µl of bacterial suspension, this would be equivalent of approximately 0.17 nmole/ml, and similarly 14% of Mel4 in the bacterial suspension is equivalent to appriximately 0.26 nmole/ml. These concentrations of potentially free peptide are much lower than the minimum inhibitory concentration (MIC) for melimine (66-132 nmole/ml) or Mel4 (26.6-106.5 nmole/ml) (Yasir et al, 2019) and so very unlikely to have had substantial effects on the results, indicating that the results are very likely to be due covalently attached peptide only. Previous results had confirmed that free melimine adopts a more ordered structure in a membrane mimetic environment (Rasul et al, 2010), but the confirmation of Mel4 in membrane mimetic environments had not been previously investigated.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations